PRIOR TO PLANTING THE SOIL AND GARDEN WORK, THE BASICS OF CREATING A PUMP UNIT - Makhmudov Fakhriddin Rahmonjon o‘g‘li; Homidov Axmadjon Baxodir o‘g‘li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The article presents the basics of creating a universal unit with an active  working  body  that  meets  the  current  agrotechnical  requirements,  and  its laboratory test option, which is necessary for preparing the plow for planting in a high-quality way and for working in garden beds.